(untitled) (BEKTI : Jurnal Pengabdian kepada Masyarakat, 2024)
This study discusses the application of Participatory Action Research (PAR) in increasing the capacity of women ecoprint artisans in the digital era. Ecoprint as a technique for dyeing fabrics with natural materials has economic and cultural potential, but craftsmen often face obstacles such as limited technical skills, digital literacy, and business management. Through PAR, craftsmen are actively involved in every stage of research, from planning, action, to reflection. The results of the study show that there is an increase in technical skills in the production of ecoprints, mastery of digital skills for promotion and marketing, and an increase in economic independence. In addition, there is a growing sense of confidence and solidarity among group members that encourage the formation of community-based businesses. The main obstacles encountered are limited digital literacy, internet access, and time, but can be overcome with gradual training, the use of simple media, and group cooperation. Thus, PAR is not only a research method, but also a means of empowering women that is able to combine economic strengthening, digital capacity building, and the preservation of local traditions in the modern era.